A Low Voltage Recycling Folded Cascode OTA based on novel CMRR Magnifier - Farsi, Mohammadreza; Monfaredi, Khalil (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
In this paper, a new recycling folded Cascode Operational Trans-conductance Amplifier (OTA) based on a novel Common Mode Rejection Ratio (CMRR) magnifier block is presented. Further, the principle of its operation is discussed in comparison with the conventional recycling folded Cascode OTA. The supply voltage is decreased in the proposed CMRR Magnifier based Recycling Folded Cascode (CMRFC) OTA, due to the elimination of the Cascode transistors. The common mode current is significantly removed by the CMRR magnifier block, which subsequently yields to a relatively higher CMRR compared with its conventional version. The DC bias voltage of the Cascode stage is also eliminated, incorporating the self Cascode structure. To provide a fair comparison, the CMRFC OTA is simulated along with its conventional version, namely the Double Recycling Folded Cascode (DRFC) OTA structure, at Cadence environment by considering the 180nm CMOS technology. The simulation results for the proposed OTA yield 53.4 dB DC-gain, 80.32 degree phase margin and 86.87 dB CMRR with 1.5 volt supply voltage, making it a suitable choice for low-voltage applications.